2018
DOI: 10.1103/physreva.98.052350
|View full text |Cite
|
Sign up to set email alerts
|

Resource theory of quantum non-Gaussianity and Wigner negativity

Abstract: We develop a resource theory for continuous-variable systems grounded on operations routinely available within current quantum technologies. In particular, the set of free operations is convex and includes quadratic transformations and conditional coarse-grained measurements. The present theory lends itself to quantify both quantum non-Gaussianity and Wigner negativity as resources, depending on the choice of the free-state seti.e., the convex hull of Gaussian states or the states with positive Wigner function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
242
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(243 citation statements)
references
References 121 publications
(193 reference statements)
0
242
0
1
Order By: Relevance
“…It has been shown that nonlinearities in the form of non-Gaussian states constitute an important resource for quantum teleportation protocols [1], universal quantum computation [2,3], quantum error correction [4], and entanglement distillation [5][6][7]. This view of non-Gaussianity as a resource for information-processing tasks has inspired recent work on developing a resource theory based on non-Gaussianity [8][9][10]. In addition, it has been found that non-Gaussianity provides a certain degree of robustness in the presence of noise [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that nonlinearities in the form of non-Gaussian states constitute an important resource for quantum teleportation protocols [1], universal quantum computation [2,3], quantum error correction [4], and entanglement distillation [5][6][7]. This view of non-Gaussianity as a resource for information-processing tasks has inspired recent work on developing a resource theory based on non-Gaussianity [8][9][10]. In addition, it has been found that non-Gaussianity provides a certain degree of robustness in the presence of noise [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A platform that is particularly promising for such applications is continuous-variable quantum optics, where large entangled graph states can be deterministically produced [5][6][7][8][9]. Even though this allows us to produce intricate quantum networks, the resulting Gaussian quantum states still have a positive Wigner function.Negativity of the Wigner function has been identified as a necessary ingredient for implementing processes that cannot be simulated efficiently with classical resources [10,11], and is therefore an essential resource [12,13] to achieve a quantum advantage. In networked quantum technologies it is, thus, crucial to generate and distribute Wigner-negativity in the nodes of a quantum network.…”
mentioning
confidence: 99%
“…1Compute the matrix Y whose existence is guaranteed by equation (35). 2Obtain g using equation (36). 3Determine σ (the ancilla state) from g using equation (8); this is possible by lemma 2.…”
Section: Lemma 7 [2]mentioning
confidence: 99%
“…In view of these limitations, it will not come as a surprise that a substantial effort has been put into developing a consistent resource theory of non-Gaussianity. Many non-Gaussianity measures have been proposed and studied in the past decade [31][32][33][34][35][36], that can be applied e.g. to bound the conversion rates between arbitrary states by means of Gaussian operations [35].…”
Section: Introductionmentioning
confidence: 99%